University extension in support of the physical space of philanthropic institutions (Research, Society and Development, 2019)
The extension project presented is included among the initiatives of Engineers Without Borders (ESF), Núcleo João Monlevade, which aim to use the knowledge acquired within the classroom, referring to engineering, to voluntarily assist society. The target institution of the project is the Municipal Foundation Crê-Ser, a philanthropic entity maintained by the Municipality of Monlevade that serves children and adolescents at personal and social risk. This article, therefore, seeks to carry out an architectural project to improve a physical space of the Crê-Ser Foundation's Welcome Unit and present, as support, the university extension, through the ESF João Monlevade. The reform is based on a redistribution of rooms, with a special focus on the kitchen and dining room, seeking to provide more accessibility, organization and comfort for children and adolescents residing on the site. The project was based on four main steps: 3D modeling of the expected result, architectural design, quantitative table of materials and work follow-up. In addition to training for the professional field, the extension project showed them the importance of service to the community. Therefore, the participation of engineering students, ESF members, enabled them to grow professionally and personally, generating individuals aware of the their social function and prepared for the labor market.